SNPs within CHRNA5-A3-B4 and CYP2A6/B6, nicotine metabolite concentrations and nicotine dependence treatment success in smokers - Hubacek, Jaroslav A; Kurcova, Ivana; Maresova, Vera; Pankova, Alexandra; Stepankova, Lenka; Zvolska, Kamila; Lanska, Vera; Kralikova, Eva (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2021)
AIM: Plasma values of nicotine and its metabolites are highly variable, and this variability has a strong genetic influence. In our study, we analysed the impact of common polymorphisms associated with smoking on the plasma values of nicotine, nicotine metabolites and their ratios and investigated the potential effect of these polymorphisms and nicotine metabolite ratios on the successful treatment of tobacco dependence. METHODS: Five variants (rs16969968, rs6474412, rs578776, rs4105144 and rs3733829) were genotyped in a group of highly dependent adult smokers (n=103). All smokers underwent intensive treatment for tobacco dependence; 33 smokers were still abstinent at the 12-month follow-up. RESULTS: The rs4105144 (CYP2A6, P<0.005) and rs3733829 (EGLN2, P<0.05) variants were significantly associated with plasma concentrations of 3OH-cotinine and with 3OH-cotinine: cotinine ratios. Similarly, the unweighted gene score was a significant (P<0.05) predictor of both cotinine:nicotine and 3OH-cotinine:cotinine ratios. No associations between the analysed polymorphisms or nicotine metabolite ratios and nicotine abstinence rate were observed. CONCLUSION: Although CYP2A6 and EGLN2 polymorphisms were associated with nicotine metabolism ratios, neither these polymorphisms nor the ratios were associated with abstinence rates.
Keywords: dospělí; tobacco dependence; cytochrom P450 CYP2A6; smoking; intensive treatment; Female; hydroxycotinine; Tobacco Use Disorder; Adult; Receptors, Nicotinic; výsledek terapie; ženské pohlaví; jednonukleotidový polymorfismus; nikotin; lidé; Polymorphism, Single Nucleotide; CYP2A6/B6; EGLN2; Treatment Outcome; nicotine-acetylcholine receptors; Cytochrome P-450 CYP2B6; proteiny nervové tkáně; Cytochrome P-450 CYP2A6; nicotine metabolism; Nerve Tissue Proteins; Male; nikotinové receptory; cytochrom P450 CYP2B6; poruchy vyvolané užíváním tabáku; lidé středního věku; cotinine; mužské pohlaví; Nicotine; Middle Aged; Humans